(untitled) (UNWE Yearbook, 2007)
The paper studies a range of critical problems in human resource management as corporate practice in Bulgaria. The approach adopted and, above all, the findings of the analysis and the current situation appraisal are intended to draw upon real achievements of the science of human resource management and the best existing foreign corporate practices in this field.The author argues that a considerable lagging behind in human resource management of Bulgarian companies as opposed to their foreign competitors, and the research in human resource management have turned into factors undermining their competitiveness – in other words, no lasting competitive advantage has been secured by means of the human factor.The paper gives a detailed outline of the approaches and specific guidelines aimed to achieve an advance in the improvement of human resource management and a boost of its contribution to increased corporate competitiveness.